Tranzakciós költségek és munkaszervezetek - Kuczi, Tibor (Szociológiai Szemle, 2024)
Based on the Transaction Costs Theory, this study is trying to find an answer to the following question: Why did big labor organizations come into existence in the beginning of the 19th Century (and why did they grow even larger hundred years later)? It draws attention to the fact, that the increase or decrease in size of the organizations is not merely due to the changes of the costs related to the use of the markets – as this would be the conclusion of the Transaction Costs Theory –, but the costs related to enforcing and controlling the labor as well. Our main thesis is that there has been a new disciplinary, efficiency constraint “technology” coming into existence, that has decreased the operational costs of labor organizations, so that establishing organizations has remained a reasonable alternate after the evolving of the modern institutional system of the market.